Analysis of the Production and Economic Indicators of Broiler Chicken Rearing in 2020–2023: A Case Study of a Polish Farm - Michalina Adaszyńska-Skwirzyńska; Paweł Konieczka; Mateusz Bucław; Danuta Majewska; Arkadiusz Pietruszka; Sławomir Zych; Danuta Szczerbińska (Agriculture)
The study aimed to analyze and evaluate the production and economic performance of a broiler chicken farm in Poland during the years 2020–2023. Production performance was assessed by comparing final body weight (BW), feed intake (FI), feed conversion ratio (FCR), and the European Performance Efficiency Factor (EPEF). Economic results were determined using the sales value, production costs, profit (direct surplus), and profitability index (PI). During the study years, the broiler rearing period lasted on average 40 days, with six production cycles each year. The average BW was found to be 2.51 kg with an average FCR of 1.54 kg/kg. For the four production years, the EPEF was calculated, reaching a high average value of 399. Broiler chicken production in Poland was profitable despite the continuously increasing production costs. In the years studied, the cost of feed accounted for 69.6–76.1% of the total production costs, chicks 15.0–19.7%, and labor costs 1.59–2.39%. In all of the analyzed production cycles, the PI of broiler chicken rearing was above 100, averaging 120.48%, and the average profit per bird was 0.46 EUR. During the study period, several negative events occurred, including the COVID-19 pandemic, the spread of avian influenza outbreaks, and consequent fluctuations in feed and poultry prices. Despite these challenges, namely the consistently rising production costs, broiler production in the study farm remained profitable.